Nature Contact and Human Health: A Research Agenda - Frumkin, Howard; Bratman, Gregory N.; Breslow, Sara Jo; Cochran, Bobby; Kahn Jr, Peter H.; Lawler, Joshua J.; Levin, Phillip S.; Tandon, Pooja S.; Varanasi, Usha; Wolf, Kathleen L.; Wood, Spencer A. (Environmental health perspectives, 2017)
At a time of increasing disconnectedness from nature, scientific interest in the potential health benefits of nature contact has grown. Research in recent decades has yielded substantial evidence, but large gaps remain in our understanding. We propose a research agenda on nature contact and health, identifying principal domains of research and key questions that, if answered, would provide the basis for evidence-based public health interventions. We identify research questions in seven domains: ) mechanistic biomedical studies; ) exposure science; ) epidemiology of health benefits; ) diversity and equity considerations; ) technological nature; ) economic and policy studies; and ) implementation science. Nature contact may offer a range of human health benefits. Although much evidence is already available, much remains unknown. A robust research effort, guided by a focus on key unanswered questions, has the potential to yield high-impact, consequential public health insights. https://doi.org/10.1289/EHP1663.